Использование понятия колориметрической функции в прикладных исследованиях - Хорошайло, Юрий Евгениевич; Ярмак, Иван Николаевич; Меняйло, Александр Дмитриевич; Сова, Анна Васильевна; Светличный, Виталий Анатольевич; Сезонова, Ирина Константиновна (Національний технічний університет "Харківський політехнічний інститут", 2019)
Предлагается устройство для измерения цветовых характеристик, которое с помощью измерительного преобразователя каждому излучению ставит в соответствие три сигнала, пропорциональных цветовых координат. Существующие устройства имеют очень много недостатков, среди которых малое быстродействие, вследствие использования инертных элементов, что делает невозможным измерения быстроизменяющихся световых потоков. В данном устройстве авторы попытались минимизировать недостатки. Также в данной статье предлагается математическая модель устройства. Уделено внимание психофизиологическому восприятию цвета.

In this paper, the authors propose a device for measuring the color characteristics of light reflected or transmitted through an optical medium. The main element of this device is the measuring transducer, which assigns to each radiation three signals proportional to the color coordinates. Existing devices have many drawbacks, among which low speed, due to the use of inert elements, which makes it impossible to measure rapidly changing light fluxes. In this device, the authors tried to minimize these limitations by using photodiodes and a microcontroller with a built-in ADC and other devices. Also in this article, a mathematical model of the device is proposed. Attention is paid to psychophysiological perception of color. As a result, we found a device that has a number of advantages over its counterparts, which makes it possible to perform color measurement with higher accuracy. The aim of the work is to study the concept of colorimetric functions in applied research, it is very well shown how to use the colorimeter functions, in which studies, and in which areas. Also, the calculations of the optoelectronic colorimeter by the method of numerical experiment and the development of practical recommendations for improving the parameters are considered. The work has developed an optoelectronic colorimeter superior to analogues in the following parameters: measurement accuracy, ease of use, range for determining colors, simplicity of the device design, reliability, cost. Color measurement is necessary in various fields, for example, for color measurements, control and color management in industrial automation, household appliances, textile industry, service stations, printing, medicine, etc.
Application of the concept of colorimetric functions in applied research
Keywords: фотодиоды; микроконтроллер; математическая модель; психофизиология зрения; photodiodes; microcontroller; mathematical model; psychophysiology of sight